2006
DOI: 10.1111/j.1365-2702.2006.01262.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of the critically ill patient and effects of implementing a nutritional support algorithm in ICU

Abstract: By using a nutritional algorithm focused on enteral nutrition, but including parenteral nutrition as a supplement, it is possible to improve the delivery of clinical nutrition in the intensive care unit patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 26 publications
2
66
0
10
Order By: Relevance
“…1,2,[11][12][13][14] In those studies, the main causes of feeding interruption were gastrointestinal intolerance (gastric reflux, vomiting, or diarrhea), interruption for medical procedures, problems with the feeding tube, and airway management (extubation). 4,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Our study showed similar results. Few studies 12,16,22,28 evaluated the risk factors, intrinsic to the patient or not, that may predispose patients to interruption of enteral nutrition.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…1,2,[11][12][13][14] In those studies, the main causes of feeding interruption were gastrointestinal intolerance (gastric reflux, vomiting, or diarrhea), interruption for medical procedures, problems with the feeding tube, and airway management (extubation). 4,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Our study showed similar results. Few studies 12,16,22,28 evaluated the risk factors, intrinsic to the patient or not, that may predispose patients to interruption of enteral nutrition.…”
Section: Discussionsupporting
confidence: 79%
“…1,2,[11][12][13][14] The main factors responsible for the interruption of enteral nutrition are gastrointestinal intolerance (gastric reflux, vomiting, or diarrhea), procedures or examinations, problems with the feeding tube, and airway management. 4,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] However, most previous studies involved evaluation of whether or not patients met their nutrition goals during the entire ICU stay rather than on a daily basis. Some factors that vary daily, such as doses of vasoactive and sedation drugs, have already been reported.…”
Section: Methodsmentioning
confidence: 99%
“…This appears to emphasize the importance of a precise determination of the energy target as well as the likelihood of achieving an improved nutritional status by using a nutritional algorithm that focused on achieving the target calorie intake within 3 days via full EN or immediate use of SPN, whenever EN fails to meet energy needs (3,31).…”
Section: Discussionmentioning
confidence: 99%
“…33,37 Specific determination of what constitutes a high GRV is unclear in the literature, and practices for assessing and addressing high GRVs vary. [38][39][40][41] Uncertainty regarding the assessment and treatment of high GRVs makes clinical decision making regarding management of GRVs difficult for practitioners.…”
Section: Intolerance Of Enteral Nutritionmentioning
confidence: 99%